MIGA Annual Report 2012 - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2013)
In fiscal year 2012, a total issue of $2.7 billion in guarantees for projects in Multilateral Investment Guarantee Agency's (MIGA's) developing member countries and an additional $10.6 million was issued under MIGA administered trust funds. This is another record high for new issuance by the Agency, the second consecutive year of this trend, and was marked by increased regional and sectoral diversification. Fifty-eight percent of projects guaranteed, accounting for 70 percent of the total volume of new coverage, address at least one of MIGA's four strategic priority areas. Fiscal year 2012 also marks the fifth consecutive year of record levels in the Agency's gross portfolio. MIGA issued $2.7 billion in guarantees in support of investments in developing countries. The Agency welcomed two new members, Niger and South Sudan, during the fiscal year. This report highlights MIGA's active support for these objectives in fiscal year 2012. It demonstrates the Agency's ability to deliver on its mandate to promote foreign direct investment into developing countries to support economic growth, reduce poverty, and improve people's lives. As the global investment environment becomes increasingly volatile, and MIGA's clients look for opportunities in frontier markets, there is greater interest in political risk-mitigation mechanisms. MIGA has positioned itself well to respond to these developments especially as a result of its stronger field presence and internal reforms over the last two years. MIGA is committed to promoting projects that promise a strong development impact and are economically, environmentally, and socially sustainable. MIGA's projects this past year demonstrate this focus in a wide range of sectors, across all regions. In fiscal year 2012 the Agency's projects in the region accounted for 24 percent of volume, twice the level of the previous year.